The Effect of Individual Modernity, Financial Literacy, and Technology Adoption on Consumptive Behavior with Lifestyle as an Intervening Variable among College Students in Malang City - Mirna Shofa Hesti; Hari Wahyono; Naswan Suharsono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to determine the influence of student consumptive behavior in terms of individual modernity, financial literacy, lifestyle, and technology adoption with lifestyle as an intervening variable. The method used is quantitative with explanatory research type . The population in this study were students in Malang city while the sample of this study were students of Malang State University, Brawijaya University, Muhammadiyah University, and Islamic University of Malang. The sampling used was multistage sampling. Data were collected by means of tests and questionnaires. Hypothesis testing was carried out using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). Based on the results of the study, it is known that individual modernity has a positive effect on consumptive behavior with a P-value of 0.000 and a t-statistic value of 51.028 while modernity has no effect on lifestyle because the P-Values value is 0.965 and a t-statistic value of 0.043. The financial literacy variable does not affect consumptive behavior because the P-Values value is 0.665 while the t-statistic value is 0.433 but the financial literacy variable has a negative effect on lifestyle with a P-Values value of 0.001 and a t-statistic value of 3.370. The technology adoption variable has a positive effect on consumptive behavior with a P-Values value of 0.020 and a t-statistic value of 2.335. The technology adoption variable also has a positive effect on lifestyle with a P-Values value of 0.000 and a t-statistic value of 4.798. The lifestyle variable has a positive effect on consumptive behavior variables with a P-Values value of 0.017 and a t-statistic value of 2.393.